Kaolin/Gum Arabic Nanocomposite as Antifungal agent against Aspergillus Flavus and Saccharomyces cerevisiae: Kaolin/Gum Arabic Nanocomposite as Antifungal agent - Shehu, Zaccheus; Lamayi, Wilson Danbature; Sabo, Adunbe Maisanda; Aliyu, Sani Ibrahim (Iraqi Journal of Science, 2019)
Kaolin/Gum Arabic nanocomposite was cheaply synthesized from Kaolin and Gum Arabic. The Kaolin/Gum Arabic nanocomposite suspension, Gum Arabic extracts and Kaolin suspension were applied as antifungal agents. The antifungal activity was tested using agar well diffusion method where by wells were made on the petri dishes with cork borer 6mm diameter in size and various concentrations (150 µg/L, 200 µg/L, and 250 µg/L) of Gum Arabic ethanol extracts, Gum Arabic /Kaolin nanocomposite, and Kaolin was propelled into the wells with the help of micropipette and the petri dishes were allowed to stand for 30 minutes to ensure proper diffusion before being incubated at 37oC. The results showed that synthesized Kaolin/Gum Arabic nanocomposite and Gum Arabic possess significant antifungal activity against Aspergillus flavus and Saccharomyces cerevisiae. No antifungal activity detected for Kaolin against Aspergillus flavus and Saccharomyces cerevisiae. From the results obtained it could be concluded that the synthesized Kaolin/Gum Arabic nanocomposite and Gum Arabic possess significant antifungal activity against Aspergillus flavus and Saccharomyces cerevisiae.